Pursuit of proteomic excellence and the excitement in Košice, Slovakia, at the 11th Central and Eastern European Proteomic Conference (CEEPC) - Gadher, Suresh; Bhide, Mangesh Ramesh; Kovarova, Hana (Expert review of proteomics, 2018)
The Central and Eastern European Proteomic Conference (CEEPC) successfully launched its second decade of proteomics in Košice, Slovakia with a program of systems biology, cellular, clinical, veterinary and sports proteomics. Whilst many conferences are struggling to attract participants, CEEPC with its outstanding track record and unique 'family - feel' packaged with excellent ambiance is thriving and bringing together proteomics experts from academia, industry, scientific specialties, clinics and precision medicine communities interested in resolving mysteries about protein functionalities in health and disease. CEEPC is also renowned for addressing humanitarian global healthcare issues, may it be ageing, chronic diseases or global epidemics. This year CEEPC intertwined with Košice Peace Marathon's pursuit of excellence in sports and initiatives including sports medicine and global peace.
Keywords: Animals; individualizovaná medicína; veterinární lékařství; Substance-Related Disorders; Proteomics; lidé; Precision Medicine; Spinal Cord Injuries; zvířata; poruchy spojené s užíváním psychoaktivních látek; proteomika; Evropa; Europe; vakcíny; Veterinary Medicine; poranění míchy; Vaccines; Humans